ТО, С ЧЕМ ВСЕ СОГЛАСНЫ (Philological Studies, 2019)
The main goal of this paper is to examine the concept of happiness, through the question what the happiness depends on. It argues that in order to achieve it, several conditions need to be fulfilled: the correct approach towards pain and suffering; deep understanding and awareness of the levels of human nature (levels of the self); adoption of human values which are inherent to the human nature itself, in order to become capable for right choices.
Keywords: happiness, fear, pain, truth, right choice, values